Arctic Justice - Wood-Donnelly, Corine; Ohlsson, Johanna (Bristol University Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Offering a unique introduction to the study of justice in the European, North American and Russian Arctic, this collection considers the responsibilities and failures of justice for environment and society in the region. Inspired by key thinkers in justice, this book highlights the real and practical consequences of postcolonial legacies, climate change and the regions’ incorporation into the international political economy. The chapters feature liberal, cosmopolitan, feminist, as well as critical justice perspectives from experts with decades of research experience in the Arctic. Moving from a critique of current failures, the collection champions a just and sustainable future for Arctic development and governance.